Left Ventricular Diastolic Parameters in Dilated Cardiomypoathy: Are We Missing Out on Something? - Kashyap, Raghava (Medknow Publications & Media Pvt Ltd, 2014)
Equilibrium radionuclide ventriculography is an established modality to assess the left ventricular (LV) systolic function in several clinical situations. Diastolic parameters can also be extracted from this investigation. The aim of our study is to assess the diastolic function of the left ventricle in cases of idiopathic dilated cardiomyopathy (IDCM) and ischemic cardiomyopathy, where systolic dysfunction has been considered of prime pathologic significance. We conducted a retrospective analysis of 89 patients who had undergone radionuclide ventriculography at our department with established diagnosis of IDCM in 59 patients and ischemic cardiomyopathy in remaining 30 patients. Peak filling rate (PFR) was assessed. The PFR was significantly lower in both patients with IDCM (median = 1.61 end diastolic volumes [EDV]/s) and ischemic cardiomyopathy (median = 2.005 EDV/s). 33% of the patients with ischemic cardiomyopathy and ejection fraction (EF) >45% had diastolic dysfunction while 25% of patients with IDCM and EF >45% had low PFR. Diastolic dysfunction can coexist in patients with dilated cardiomyopathy and even in patients with preserved LV EF. Routine evaluation of diastolic function in patients with heart failure can help in elucidation of pathogenesis and management of patients.